2020
DOI: 10.3390/land9120531
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry as Policy Option for Forest-Zone Oil Palm Production in Indonesia

Abstract: With 15–20% of Indonesian oil palms located, without a legal basis and permits, within the forest zone (‘Kawasan hutan’), international concerns regarding deforestation affect the totality of Indonesian palm oil export. ‘Forest zone oil palm’ (FZ-OP) is a substantive issue that requires analysis and policy change. While spatial details of FZ-OP remain contested, we review literature on (1) the legal basis of the forest zone and its conversion, (2) social stratification in oil palm production (large-scale, plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 146 publications
0
13
0
Order By: Relevance
“…The term smallholder covers a wide variety of different oil palm models. However, both official statistics, and a sizable fraction of research studies, report smallholder oil palm as a single entity ( Jelsma et al, 2017 ; Schoneveld et al, 2019a , Schoneveld et al, 2019b ; Purwanto et al, 2020 ). Different oil palm models likely result in different social and economic outcomes, though lack of standardised methods, indicators and definitions has meant that few comparative research attempts have been made ( Hidayat et al, 2015 ; Schoneveld et al, 2019a , Schoneveld et al, 2019b ).…”
Section: Background and Contextmentioning
confidence: 99%
“…The term smallholder covers a wide variety of different oil palm models. However, both official statistics, and a sizable fraction of research studies, report smallholder oil palm as a single entity ( Jelsma et al, 2017 ; Schoneveld et al, 2019a , Schoneveld et al, 2019b ; Purwanto et al, 2020 ). Different oil palm models likely result in different social and economic outcomes, though lack of standardised methods, indicators and definitions has meant that few comparative research attempts have been made ( Hidayat et al, 2015 ; Schoneveld et al, 2019a , Schoneveld et al, 2019b ).…”
Section: Background and Contextmentioning
confidence: 99%
“…A final group of five papers (Table 3) considered the agricultural-forestry interface, in policy and institutional terms, as essential to the further development of agroforestry. With 15-20% of Indonesian oil palms located, without a legal basis and permits, within the forest zone ('Kawasan hutan'), international concerns regarding deforestation affect the totality of Indonesian palm oil exports [17]. Data analysis showed that 'Forest zone oil palm' (FZ-OP) is a substantive issue with substantial geographic variation in intensity within Indonesia that requires analysis and policy change.…”
Section: Addressing the Agricultural-forestry Policy Interfacementioning
confidence: 99%
“…Where private tenure control has long been seen as essential for economic progress, de facto local community institutions have resurfaced in various contexts (van Noordwijk 2017; He 2021). The observation that around 15% of oil palms in Indonesia are growing within the state forest zone, while there is no legal way this could happen (Purwanto et al 2020), indicates a challenge for all involved. For more information about work on governing forests, agroforestry and trees for delivering on the SDGs conducted within FTA, see Highlight No.14 in this series (Minang et al 2021a).…”
Section: Rights Governancementioning
confidence: 99%